Análisis de la gestión del Departamento Financiero del Gobierno Autónomo Descentralizado Municipal del cantón Alfredo Baquerizo Moreno (Jujan) - Castro Eguez, Adrian Javier (2021)
The analysis of financial management allows the Decentralized Autonomous Government Alfredo Baquerizo Moreno of the Jujan canton to establish a set of interrelated processes to provide effective and efficient financial support for its proper operation and control of the economic resources it has in order to use them in a correct and timely manner. With the present investigation it is tried to approach to observe the handling of the financial management to contribute to the analysis of the influential key factors that reflect the mismanagement of the economics of the company through qualitative, deductive-inductive research to study the laws, regulations, pertaining functions to the municipal GAD of Jujan, in addition the data collection technique will allow us to relate more to the issue and detail each of its inconsistencies that cause there to be no solvency liquidity in the institution.